2021
DOI: 10.1002/adma.202106021
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Theory for Domain Walls in Oxide Ferroelectrics Based on Interatomic Interactions and its Implications for Collective Material Properties

Abstract: Domain walls separating regions of ferroelectric material with polarization oriented in different directions are crucial for applications of ferroelectrics. Rational design of ferroelectric materials requires the development of a theory describing how compositional and environmental changes affect domain walls. To model domain wall systems, a discrete microscopic Landau–Ginzburg–Devonshire (dmLGD) approach with A‐ and B‐site cation displacements serving as order parameters is developed. Application of dmLGD to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…It is noted that small c/a, which is obtained when the lattice constant parallel (perpendicular) to polarization decreases (increases), tends to reduce the DW formation energy. 43,44…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that small c/a, which is obtained when the lattice constant parallel (perpendicular) to polarization decreases (increases), tends to reduce the DW formation energy. 43,44…”
Section: Resultsmentioning
confidence: 99%
“…[30] In recent DFT studies, the lower energy state has been found to be the antiparallel B-site displacement direction when competing between being displaced in the parallel (single domain) and antiparallel (multiple domains) directions, as shown in Figure 3a. [31] These results have been explained using the simple argument of the minimization of electrostatic energy. In the AFE state, the electrostatic energy is reduced with the antiparallel arrangement while increasing the repulsion between the A-site and B-site.…”
Section: Phase Diagram and Phase Transitionsmentioning
confidence: 98%
“…Figure 3. a) Energy difference between AFE and FE phases as a function of lattice parameter c for BTO (BaTiO 3 ), KNO (KNbO 3) and PTO (PbTiO 3 ), wherein the energies have been calculated for structures with a fixed A-site and oxygen octahedron cage. Reproduced with permission [31]. Copyright 2021, John Wiley and Sons.…”
mentioning
confidence: 99%
“…In traditional semiconductor p-n junction solar cells, the position of quasi Fermi level limits that the energy difference of electron hole pair in thermal equilibrium state that cannot exceed its bandgap (the Shockley and Queisser limit) (SQL) [ 6 ]. From this point of view, although the specific microscopic mechanism of BPE is still controversial [ 7 ], it must be different from the traditional p-n junction space depletion layer, because both theoretical calculation and experimental results show that [ 8 , 9 ], the open circuit voltage (Voc) of ferroelectric materials (or localized polar materials) [ 10 ] can exceed the limit of SQL, reaching two to four orders of magnitude higher than the bandgap [ 11 ], which enables ferroelectric photovoltaic devices with significant potential to be applied in multifunctional optical–electrical systems [ 12 ].…”
Section: Introductionmentioning
confidence: 99%